Patients' experiences of remote communication after pacemaker implant: The NORDLAND study - Catalán-Matamoros, Daniel; Lopez-Villegas, Antonio; Lappegård, Knut Tore; Lopez-Liria, Remedios (PLOS ONE, 2019)
Source at https://doi.org/10.1371/journal.pone.0218521. Background - The concept of ‘patient experience’ has become central to how to improve healthcare. Remote communication with patients is today a frequent practice in healthcare services, showing similar outcomes to standard outpatient care while enabling cost reduction in both formal and informal care. The purpose of this study was to analyse the experiences of people with telemonitoring pacemakers. Methods - Patients were randomly allocated to either the telemonitoring or hospital monitoring follow-ups. Using the ‘Generic Short Patient Experiences Questionnaire’ (GS-PEQ), as well as an ad-hoc survey from the ‘telehealth patient satisfaction survey’ and ‘costs survey’, patients’ experiences were measured six months after the pacemaker implant in a cohort of 50 consecutive patients. The mean age was 74.8 (± 11.75) years and 26 (52%) patients were male of which 1 was lost in follow-up. Finally, 24 patients were followed up with standard hospital monitoring, while 25 used the telemonitoring system. Differences in baseline characteristics between groups were not found. Results - Findings showed overall positive and similar experiences in patients living with telemonitoring and hospital monitoring pacemakers. Significant differences were found in GS-PEQ concerning how telemonitoring patients received less information about their diagnosis/afflictions (p = 0.046). We did not find significant differences in other items such as ‘confidence in the clinicians’ professional skills’, ‘treatment perception adapted to their situation’, ‘involvement in decisions regarding the treatment’, ‘perception of hospital organisation’, ‘waiting before admission’, ‘satisfaction of help and treatment received’, ‘benefit received’, and ‘incorrect treatment’. Conclusions - The remote communication of pacemakers was met with positive levels of patients’ experiences similarly to patients in the hospital monitoring follow-up. However, telemonitoring patients received less information. ...